2013
DOI: 10.1002/ajt.12218
|View full text |Cite
|
Sign up to set email alerts
|

Pathology of Resolving Polyomavirus-Associated Nephropathy

Abstract: These authors contributed equally. Control of polyomavirus BK (BKV) is achieved by reducing immunosuppression allowing an effective BKV-specific T-cell response. The morphology of resolving BKV-associated nephropathy (PyVAN) has not been systematically investigated. Ninety-nine surveillance biopsies of 35 patients with BKV viremia treated exclusively by immunosuppression reduction were scored according to Banff criteria and grouped relative to BKV viremia as pre-, increasing, decreasing and post-BKV viremia. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
19
0
3

Year Published

2013
2013
2019
2019

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(24 citation statements)
references
References 40 publications
2
19
0
3
Order By: Relevance
“…Besides a higher incidence of viremia, our patients also presented a higher rate (14.7%) of PyVAN (bx‐proven (6%) and presumptive PyVAN (8.7%). The incidence of SV40 negative in the presumptive PyVAN biopsies, shown here, are consistent with the findings of negative SV40 in 60% of the biopsies and suggests, as mentioned by others that renal biopsies may not be a gold standard to establish the diagnosis of PyVAN in screening programs. This finding is relevant to support the approach of reducing immunosuppression at a specific level of viremia regardless of a renal biopsy.…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…Besides a higher incidence of viremia, our patients also presented a higher rate (14.7%) of PyVAN (bx‐proven (6%) and presumptive PyVAN (8.7%). The incidence of SV40 negative in the presumptive PyVAN biopsies, shown here, are consistent with the findings of negative SV40 in 60% of the biopsies and suggests, as mentioned by others that renal biopsies may not be a gold standard to establish the diagnosis of PyVAN in screening programs. This finding is relevant to support the approach of reducing immunosuppression at a specific level of viremia regardless of a renal biopsy.…”
Section: Discussionmentioning
confidence: 94%
“…The comparison of bx‐proven and presumptive PyVAN showed that resolving presumptive PyVAN still presented inflammatory cells infiltrating the interstitium along with tubulitis. These findings had already been shown by others who demonstrated an increase in intra‐epithelial lymphocytes and interstitial inflammation during the resolving phase of PyVAN, culminating with some degree of tubular atrophy and interstitial fibrosis (IFTA) . The virus‐specific T cells play a major role in elimination of reactivated polyoma virus.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, in 2 small series delayed platelet engraftment was not found to be a significant variable in the development of HC 21 or in children with severe HC 31 . We also analyzed serum creatinine because of its association with platelet dysfunction 61 and BK virus-induced nephropathy 62, 63 , but observed no relation to risks or severity of HC. Uhm et al found worsening renal function during HC, but concluded that this resulted from concurrent CMV therapy rather than direct nephrotoxic effect of HC 10 .…”
Section: Discussionmentioning
confidence: 99%
“…If the disease is detected at an early stage, a reduction in the immunosuppression is often enough to clear the BKPyV viremia and stop the progression of disease (129)(130)(131). In a recent histopathological study of 35 patients with PyVAN treated by reduction in immunosuppression alone, 83% of the patients showed stable or improved allograft function 2 years later, while 2 patients (6%) experienced clinical rejection (132). Interestingly, the morphological pattern of resolving PyVAN could not be distinguished from rejection and revealed intraepithelial lymphocytes and interstitial inflammation.…”
Section: Treatment Pyvanmentioning
confidence: 99%